Análise dos efeitos de expansão e crise econômica sobre os diferenciais de renda por gênero no Brasil via regressão quantílica - Oliveira, Bruna Gabrielle Santos Gonçalves Oliveira (Universidade Federal de São Carlos, 2023)
This study investigates wage inequalities between men and women in Brazil, considering variables such as race, region, job position, occupational group, hours worked, age, and educational level. The objective is to understand the persistent income disparities in the labor market and contribute to the formulation of public policies more aligned with Brazilian realities. The analysis is based on the hypothesis that economic crises exacerbate these inequalities. To this end, the study examines three distinct periods: a year of economic expansion (2007), the beginning of Brazil's contemporary economic crisis (2015), and a year marked by the intensification of the crisis due to the pandemic (2021). The data used were drawn from PNAD (2007, 2015) and PNADc (2021). Unlike other studies on the subject, the estimates were conducted using Quantile Regression, based on the Mincerian equation. This method allows for the evaluation of labor returns at various points of the income distribution, not just the average. The results indicate significant wage disparities between men and women, as well as within each group. Additionaly, it was possible to conclude that these income gaps increase during periods of economic crisis.
The effects of economic expansion and economic crises on the gender wage gap in Brazil: a quantile regression analysis
Keywords: Mercado de trabalho; Desigualdade entre gêneros; Regressão quantílica; Políticas públicas; Dados PNAD; Brazilian labor market; Gender inequality; Quantile Regression; Public Policies; PNAD data; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; 5. Igualdade de Gênero